The significance of meristic changes in the flowers of Sapotaceae (2016)
Sapotaceae belongs to the heterogeneous order Ericales and exhibits extensive diversity in floral morphology. Although pentamery is widespread and probably the ancestral condition, some clades are extremely variable in merism, with fluctuations between tetramery to hexamery and octomery, affecting different floral organs to different degrees. We assessed the different states of merism in Sapotaceae to determine the evolution of this character among different clades. The floral morphology and development of nine species from eight genera were investigated using scanning electron microscopy (SEM). Furthermore, floral characters related to merism were mapped onto a phylogenetic tree to analyse the distribution and evolutionary significance of merism in the family. Developmental evidence shows that changes in merism are linked to a concerted multiplication of organs among whorls and an increase in whorls through the displacement of organs. Although pentamery is reconstructed as the ancestral condition, a reduction to tetramery or an increase to a higher merism (mainly hexamery or octomery) has evolved at least five times in the family. Fluctuations in merism between different whorls are not random but occur in a coordinated pattern, presenting strong synapomorphies for selected clades. Octomery has evolved at least twice, in Isonandreae from tetramery and in Sapoteae-Mimusopinae from pentamery. Hexamery has evolved at least three times, independently in Northia, the Palaquium clade of Isonandreae and derived from octomery in Sapoteae-Mimusopinae. Three possibilities of merism increase have been identified in Sapotaceae: (1) a concerted increase affecting all organs more or less equally (Palaquium clade of Isonandreae, Sapoteae); (2) a coordinated increase in petals, stamens and mostly carpels without effect on sepals (Labourdonnaisia, Payena-Madhuca clade of Isonandreae); (3) an increase in carpels independently of other organs (Burckella, Letestua, Labramia, etc.). A major shift affecting all Sapotaceae, except Isonandreae, is the sterilization or loss of the antesepalous stamen whorl. The presence of two fertile stamen whorls in Isonandreae indicates a possible reversal or a retained plesiomorphy. In a number of genera, stamens are secondarily increased independently of changes in merism. Descriptions of flowers listing only organ numbers are thus misleading in the inference of evolutionary relationships, as they do not differentiate between changes in merism affecting the number of perianth whorls and other changes affecting the androecium, such as sterilization, loss or occasional doubling of antepetalous stamens. © 2016 The Linnean Society of London.